Spatio-Temporal Analysis of Ground Movement Using Unmanned Aerial Vehicle Photogrammetry in Gampong Lamkleng, Aceh Besar - Nabila Amalia; Syamsidik Syamsidik; Nazli Ismail (International Journal of Disaster Management, 2023)
Ground movement is one of the most frequent disasters causing major damages in Indonesia. Unmanned Aerial Vehicle (UAV) has been widely used as a rapid observation method to obtain detailed characterization of ground movement. Often, active landslide area is difficult to access. This hinders close monitoring and observations of the ground movement. This study aims to demonstrate the use of UAV as tools for monitoring and observations on active ground movement area and to validate the results. For this purpose, the study was conducted at Gampong Lamkleng, Aceh Besar-Indonesia using spatio-temporal analysis by UAV photogrammetry. The UAV was chosen because it is easy to use, practical, and safe for landslide area that are relatively small and difficult to reach. Aerial photographs were processed using the Agisoft Metashape software in modeling and analyzed using Quantum GIS (QGIS) and ArcGis. The observation results show that the largest ground movement occurred in January 20 to 23, 2021 which was related to precipitation rates measured at a nearby rainfall station. The movement volume was 1,411.063 m3 and a rate of ground movement reaching 0.69 m/day due to heavy rain. The estimated value of losses is IDR 1,055,854,000. The UAV images analysis were compared to actual ground elevation measured using Real-Time Kinematic (RTK). The validation show that the accuracy based on comparison between photogrammetric and RTK measurement was at agreeable rate (99%). Otherwise, the accuracy performed on 19 check point using Root Mean Square Error analysis found that the accuracy was still very low. The low RMSE value is due to the georeferencing process using the Ground Control Point not being carried out.